2000
DOI: 10.1034/j.1399-3038.2000.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a partially hydrolyzed infant formula with two extensively hydrolyzed formulas for allergy prevention:A prospective, randomized study

Abstract: The aim of this study was to compare the allergy-preventive effect of a partially hydrolyzed formula with two extensively hydrolyzed formulas, in infants with a high risk for development of allergic disease. High-risk infants from four Danish centres were included in the period from June 1994 to July 1995. Five-hundred and ninety-five high-risk infants were identified. High-risk infants were defined as having biparental atopy, or a single atopic first-degree relative combined with cord blood immunoglobulin E (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
143
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 27 publications
4
143
1
5
Order By: Relevance
“…As 80–90% of respiratory allergic diseases in children and young adolescents are associated with sensitization to aeroallergens (mainly pollen and house dust mites), it is reasonable to hypothesize that IgE might be involved. However, we did not observe any association between specific IgE measured in serum and hydrolyzates at 15 years, which is consistent with our findings at six and ten years 21, 27 and with reports from the literature 17, 18, 19. Therefore, IgE does not appear to be involved in the observed findings in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As 80–90% of respiratory allergic diseases in children and young adolescents are associated with sensitization to aeroallergens (mainly pollen and house dust mites), it is reasonable to hypothesize that IgE might be involved. However, we did not observe any association between specific IgE measured in serum and hydrolyzates at 15 years, which is consistent with our findings at six and ten years 21, 27 and with reports from the literature 17, 18, 19. Therefore, IgE does not appear to be involved in the observed findings in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Most 11, 12, 13, 14, 15, 16, 17, 18, 19 but not all 7 randomized, controlled trials that have compared different partially and/or extensively hydrolyzed formulas with standard cow′s milk formula (CMF) have confirmed some degree of preventative effect on allergies in the first 2–3 years of life. Results appear especially consistent for eczema 20 within the first year of life.…”
mentioning
confidence: 99%
“…Sample size: a reduction in cumulative incidence of eczema from 30% to 20% at 12 months was considered clinically relevant 17, 18, 19. Assuming 15% dropout, this study required 350 infants randomized before 4 weeks in each arm, to have 80% power to detect this reduction in eczema, using two‐tailed chi‐squared test at a significance of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…49,51,52 Two of these studies found no significant effect, 51,52 and a third study found an OR of 0.45 (95% CI: 0.22-0.94) for partially hydrolyzed formula versus cow milk formula. 49 Three more studies [53][54][55] examined prolonged feeding of extensively hydrolyzed formula compared with partially hydrolyzed formula in 411 infants at high risk of developing allergy. None of these studies found a significant difference in the incidence of atopic dermatitis between the 2 feeding groups.…”
Section: Role Of Hydrolyzed Formula On the Development Of Atopic Diseasementioning
confidence: 99%
“…However, using the criteria of a 2006 Cochrane review, 41 only 14 randomized or quasirandomized (eg, using alternation) trials in term infants compared the use of partially or extensively hydrolyzed formula with the use of human milk or an adapted cow milk formula. [42][43][44][45][46][47][48][49][50][51][52][53][54][55] All of these trials have followed up with at least 80% of study participants. It is important to note that none of these studies reported any adverse effects, including any adverse effect on infant growth.…”
Section: Role Of Hydrolyzed Formula On the Development Of Atopic Diseasementioning
confidence: 99%